A case of congenital anosmia. (29th November 2016) - Vivekananda, Umesh; Khandanpour, Nader; Omer, Salah
Abstract : An 18-year-old girl presented with inability to smell from birth. She had no symptoms to suggest an endocrine disturbance. Anosmia was confirmed on bedside testing. A diagnosis of congenital anosmia was made. A 3T MRI scan (figure) of this patient revealed no olfactory bulbs but developed olfactory sulci. The rest of the brain including corpus callosum was normal. The differential diagnosis for congenital anosmia is Kallman syndrome. However, in Kallman syndrome, the olfactory sulci would also be absent.